Punishment for War Crimes: Duty--or Discretion? - Michigan Law Review (1971)
In 1968, a movie called The Graduate received wide critical acclaim for characterizing the malaise of youthful America. For many, the scene most representative of contemporary irrelevance took place during the protagonist's homecoming party, at which a businessman, with grave and repetitive insistence, encouraged the recent college graduate to enter the plastics industry. In a CBS-TV news interview on November 24, 1969, Paul D. Meadlo revealed his participation in an incident in Vietnam that has captured the horrified attention of the nation. Meadlo, twenty-three years old, is a machine operator in a Terre Haute, Indiana plastics factory